PENANAMAN NILAI-NILAI MULTIKULTURAL DALAMiiPEMBELAJARAN PENDIDIKANi AGAMAISLAM DI SMP ISLAMiiMA’ARIF 02 JANTI MALANGi - Ahmad Khairul Anam; Rosichin Mansur; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to describe and analyze about: 1) Implementation of planting multicultural values in ilearning Islamic ireligious education; 2) Methods of planting multicultural values in learning Islamic religion; 3) Supporting factors and inhibiting multicultural values in learning Islamic education. This type of research is qualitative research. The research subjects were Islamic Educationi teachers, principals, and VII grade students of Islamic Middle School Ma'arif 02 Janti Malang. The technique used in determining the research subject was purposive sampling technique. The technique of collecting data is by interview, observation, and documentation. Research findings that the implementation of the planting of multicultural values in the learning of Islamic education includes religious values, honesty values, tolerance values, democratic values, unity values, and values of justice. The method used is the exemplary method and habituation method. the encouragement of teachers to guide students to improve multicultural values, and habituation. Inhibiting factors are family factors that are less supportive, lacking social life, student personality factors, and understanding of students who are too far away, both in religion or multicultural values. planting multicultural values towards students, namely the growth of mutual tolerance, respect, accepting the opinions of others, cooperating, not hostile, and the absence of conflict due to differences in culture, ethnicity, language, customs and religion. Keywords: multicultural values, learning, islamic education